2000
DOI: 10.4141/p99-170
|View full text |Cite
|
Sign up to set email alerts
|

Wind reduces growth and yield but not net leaf photosynthesis of primocane-fruiting red raspberries (Rubus idaues L.) in the establishment years

Abstract: Privé, J.-P. and Allain, N. 2000. Wind reduces growth and yield but not net leaf photosynthesis of primocane-fruiting red raspberries (Rubus idaues L.) in the establishment years. Can. J. Plant Sci. 80: 841-847. Four primocane-fruiting (PF) red raspberry cultivars, Bogong, Autumn Cascade, Heritage and Dinkum, were grown in exposed or sheltered (50% permeable artificial windbreak) sites fully exposed to prevailing winds in Bouctouche, NB. Shelters were erected at the beginning and removed at the end of each gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Goulart, unpublished data). A recent study in New Brunswick, however, indicated that wind did not affect photosynthesis (Privé and Allain, 2000), therefore perhaps other factors such as humidity or soil moisture were also involved. In addition, the more diffuse light conditions in the tunnel may have resulted in more light reaching lower leaves, and increased photosynthesis rates.…”
Section: Discussionmentioning
confidence: 92%
“…Goulart, unpublished data). A recent study in New Brunswick, however, indicated that wind did not affect photosynthesis (Privé and Allain, 2000), therefore perhaps other factors such as humidity or soil moisture were also involved. In addition, the more diffuse light conditions in the tunnel may have resulted in more light reaching lower leaves, and increased photosynthesis rates.…”
Section: Discussionmentioning
confidence: 92%
“…Heat unit sum accumulation has been correlated with raspberry cane growth (Hoover et al, 1989). Furthermore, protecting canes from wind increased their growth and yield (Privé and Allain, 2000). Because plants in the open field received more water from rainfall, less irrigation was needed, thus they were fertigated less frequently and received less nutrient solution.…”
Section: Discussionmentioning
confidence: 99%
“…The stabilisation of canes promoted increase of leaf area by 41% to 159% depending on genotype, compared to control canes. The tunnels, similarly to wind shelters (Prive and Allain, 2000), improve a better microclimate, and provide more favourable conditions for cane growing, flower pollination and development of berries.…”
Section: Discussionmentioning
confidence: 99%
“…Some genotypes are not very sensitive to climate, and for these no differences in bud development are observed (Dale, 2008). In experiments with autumn raspberries, the use of a wind shelter increased yield, as shoots were longer, with more internodes and fruit laterals, and the leaf surface was larger (Prive and Allain, 2000). A clear knowledge of raspberry flower initiation and dormancy indicates that the plant can be manipulated in many ways so that the fruits can be produced throughout the year.…”
Section: Introductionmentioning
confidence: 99%